Lipid intensive drug therapy for sepsis pilot: A Bayesian phase I clinical trial. Issue 6 (18th November 2020) - Guirgis, Faheem W.; Black, Lauren Page; DeVos, Elizabeth; Henson, Morgan; Ferreira, Jason; Miller, Taylor; Rosenthal, Martin; Leeuwenburgh, Christiaan; Kalynych, Colleen; Moldawer, Lyle; Jones, Lisa; Crandall, Marie; et al.
Abstract: Objectives: Cholesterol may be protective in sepsis. Patients with early sepsis may have critically low cholesterol levels that are associated with poor outcomes. The study objective was to test the safety of a fish oil–containing lipid injectable emulsion for stabilizing early cholesterol levels in sepsis. Methods: Phase I Bayesian optimal interval design trial of adult patients with septic shock (Sequential Organ Failure Assessment score ≥4 or vasopressor dependence). Using sequential dose escalation, participants received 2 doses of 1.0 to 1.6 g/kg of lipid emulsion (Smoflipid 20% lipid emulsion) within 48 hours of enrollment. Cholesterol levels, function, and organ failure were assessed serially during the first 7 days of hospital admission. Measurements and Main Results: A total of 10 patients with septic shock were enrolled. One patient withdrew for social reasons. Another patient had an unrelated medical complication and received 1 drug dose. Of 9 patients, mean age was 58 years (SD 16), median Sequential Organ Failure Assessment was 8, and 28‐day mortality was 30%. No serious adverse events related to lipid infusion occurred. The six occurrences of non‐serious adverse events possibly related to lipid infusion included hyperglycemia (1), elevated triglycerides (3), anemia (1), and vascular access redness/pain (1) for all doses. The mean change in total cholesterol levels from enrollment was −7 (SD 16.6) at 48 hours and 14 (SD 25.2) at 7 days. Conclusions: Fish oil–containing lipid emulsion administration during early septic shock was safe. Further studies are needed to assess effects on cholesterol levels, function, and organ failure. Clinical Trial Registration: NCT03405870.